Why more West than East German firms export - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2007)
Using unique new data and a recently introduced non-linear decomposition technique this paper shows that the huge difference in the propensity to export between West and East German plants is to a large part due to differences in firm size and human capital intensity.
Keywords: F14; 330; Exportindustrie; Verarbeitendes Gewerbe; Vergleich; Betriebsgröße; Humankapital; Alte Bundesländer; Neue Bundesländer; Deutschland